Managing the transition to electric mobility in Chinese automotive subsidiaries of MNCs. (1st January 2012) - Proff, Heike
With the transition to electric mobility, foreign manufacturers and suppliers want to defend or even expand their previously high market shares despite increasing Chinese competition and want to continue to tap Chinese market opportunities. This article examines the challenges for the Chinese subsidiaries of multinational automotive companies in the transition to electric mobility. These consist of being unable to serve the largest market in the world adequately, failing to test the new technology adequately, being unable to raise the resources needed to finance electric mobility and being unable to handle the divergent management logics of the old and new drive technologies properly. To carry out the study, structured interviews with experts in China were conducted alongside the theoretical deduction of hypotheses in 2010.